2017
DOI: 10.15361/1984-5529.2017v45n2p145-153
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of soybean cultivars to the root-knot nematode Meloidogyne javanica

Abstract: Meloidogyne javanica is one of the main nematodes that attack soybean crops and although genetic resistance is the ideal control measure, few cultivars are described as resistant among the innumerous cultivars recommended for the Central Region of Brazil. In this context, we aimed to evaluate the reaction of 29 soybean cultivars to M. javanica. Two experiments were conducted under greenhouse conditions in a completely randomized design with six replications. The plants were inoculated with a suspension of 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…Although 21 genotypes had Rfs < 1 in the 1st experiment, none of them except PRF-GCI7 and DM 6.2i RR could maintain the resistance trait (Rf < 1) under the higher temperature regime of the 2nd experiment. The present results hence coincide with those of Teixeira et al (2017) who showed that only the M. javanica resistance trait could be verified for two of the 14 soybean genotypes that were classified as resistant in an initial glasshouse experiment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although 21 genotypes had Rfs < 1 in the 1st experiment, none of them except PRF-GCI7 and DM 6.2i RR could maintain the resistance trait (Rf < 1) under the higher temperature regime of the 2nd experiment. The present results hence coincide with those of Teixeira et al (2017) who showed that only the M. javanica resistance trait could be verified for two of the 14 soybean genotypes that were classified as resistant in an initial glasshouse experiment.…”
Section: Discussionsupporting
confidence: 92%
“…This is not unexpected since such anomalies have been reported from other studies for M. incognita-and/or M. javanica-resistant genotypes (Fourie et al 2006;Sharma et al 2006). Also, the Brazilian 'BRSGO Raissa' was classified as susceptible to M. javanica (Embrapa 2011), while Teixeira et al (2017) reported it as resistant. Such contrasting results may be due to the occurrence of different races or pathotypes or virulent populations of the target root-knot nematode species, as well as abiotic or biotic factors that occur in different climatic zones (Hussey and Janssen 2002) where soybean is grown.…”
Section: Discussionsupporting
confidence: 71%
“…An early study also identified three soybean cultivars, Centennial, Forrest, and Hartwig, that were resistant against both the soybean cyst nematode (race 3) and M. incognita (race 3) [109]. Out of 29 soybean cultivars tested in Brazil for their resistance against M. javanica, none were found to be resistant, with only two (TMG 1288 RR and NS 8270) having moderate levels of resistance [110]. In Pakistan, local soybean varieties/lines viz.…”
Section: Host Plant Resistancementioning
confidence: 99%
“…Other studies, in order to identify molecular markers related to M. javanica in PI 230977 [10] used 2,000 eggs, while in PI 595099 and CD 201 used 3,000 eggs [12]. In the screening studies for resistance in Brazilian cultivars, it was used 2,000 eggs [27] and 4,000 eggs [28]. Susceptible known accessions used in other studies, as cv.…”
Section: Javanica Reaction In the Soybean Accessionsmentioning
confidence: 99%